Developing Java Software for Representation, Acquisition and Management of Strategy Knowledge - Naghashyan, Zaven; Pogossian , Edward (Mathematical Problems of Computer Science, 2021)
Technical solutions for representing and managing concepts of strategy knowledge for Java based software package and the framework of personalized and communalized knowledge acquisition is described. The following six units are considered - Game Tree Organization, Instances Matching Oriented Classes, Dynamic Class Hierarchy Management, Web Based Graphical Interface and Relations Builder Procedure as well as ideology of knowledge learning and evaluation. The solutions develop and enhance classical object oriented approaches to be used for representation and management of the concepts of strategy knowledge, their learning and evaluation.